A Hybrid Delphi-AHP Based Analysis of Construction Project - Specific Success Factors in Emerging Markets: The Case of Ethiopia. Issue 1 (1st January 2021) - Belay, Solomon; Goedert, James; Woldesenbet, Asregedew; Rokooei, Saeed
Abstract: Literature highlights that the success of construction projects differs in various attributes. However, only a few empirical studies have been conducted to examine the inter-sectorial aspects of critical success factors in developing countries. Hence, this study aims to investigate the comparative analysis of success factors in public and private sectors across the Ethiopian construction industry. A structured questionnaire matrix was prepared based on the hierarchical model developed through a systematic literature review. Then, the present study introduced a Delphi–Analytic Hierarchy Process (AHP) technique to analyze successful attributes in the Ethiopian construction sector. The two rounds of Delphi–AHP survey were conducted through a panel of experts working in different construction firms including owner, consultant, contractor, and academia. The result indicates that the top three ranked critical success factors (CSFs) in the private sector are clear project goals, financial capacity of contractor, and competency of consulting firm. However, CSFs such as adequacy of funds, political environment, and clear project goals are the major CSFs in public construction sector. More so, the findings reveal that there was a consensus among respondents on the rankings of success factors. The study provides practical implications and key recommendations regarding CSFs to enhance project management performance in the Ethiopian construction sector.